2022
DOI: 10.1093/ckj/sfac040
|View full text |Cite
|
Sign up to set email alerts
|

Kidney health for all: bridging the gap in kidney health education and literacy

Abstract: The high burden of kidney disease, global disparities in kidney care, and poor outcomes of kidney failure bring a concomitant growing burden to persons affected, their families, and carers, and the community at large. Health literacy is the degree to which persons and organizations have or equitably enable individuals to have the ability to find, understand, and use information and services to make informed health-related decisions and actions for themselves and others. Rather than viewing health literacy as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This approach probably facilitated a closer nurse-patient relationship to be established and face-to-face teaching has been recommended to improve fluid and dietary adherence in those on HD (Yangöz et al, 2021). Choi and Choi (2021) found that nurse-led, teach-back interven- Langham et al, 2022;Shah et al, 2021). As those with limited health literacy mostly rely on HCPs for information, the delivery of health information in a clear and concise manner using simple language and nonmedical terms is essential to facilitate understanding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach probably facilitated a closer nurse-patient relationship to be established and face-to-face teaching has been recommended to improve fluid and dietary adherence in those on HD (Yangöz et al, 2021). Choi and Choi (2021) found that nurse-led, teach-back interven- Langham et al, 2022;Shah et al, 2021). As those with limited health literacy mostly rely on HCPs for information, the delivery of health information in a clear and concise manner using simple language and nonmedical terms is essential to facilitate understanding.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, none of the studies included in the present review investigated health literacy as an outcome of using teach‐back as strategy to improve health literacy and self‐management. Health provider communication, patient reinforcement, and education and training can benefit patients' health literacy (Dinh et al, 2022; Langham et al, 2022; Shah et al, 2021). As those with limited health literacy mostly rely on HCPs for information, the delivery of health information in a clear and concise manner using simple language and nonmedical terms is essential to facilitate understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…World Kidney Day is an annual global awareness campaign held on the second Thursday of March with the primary objective of raising awareness about the importance of kidney health and reducing the burden of kidney disease worldwide. As practicing nephrologists, this day holds profound significance as it allows us to reflect on our experiences and contemplate future directions in kidney care and research (1,2).…”
Section: Introductionmentioning
confidence: 99%